Boiler drum level single loop Fuzzy Logic Control at model BDT921: article - Engku Abdul Hamid, Engku Maimona; Ahmad, Mohd Aizad (2016)
This study had been conducted to determine the best input and output parameter Fuzzy Logic Controller and to study the performance of level process using Fuzzy Logic System. For the analysis of performance of Fuzzy Logic, the boiler drum level controller at model BDT921 PCTS data will be used by using Emerson programming. This is done by tuning the Fuzzy Logic Control (FLC) variables which are analyzed the error, change of error and change of output. The collection of data on the variables that will contribute to yield the best performance output is obtained. All these data are then inserted in Emerson programming to be determined the settling time, decay ratio, number of oscillation and integral analysis error (IAE) analysis for each variable could be performed. In conclusion, based on the tuning FLC parameters such as fast response and settling time, small decay ratio, no overshoot, short distance peak to set point, small integral absolute error (IAE) analysis are the criteria that would be final decision for the best performance of Fuzzy Logic Control system